HUBUNGAN POLA PENGASUHAN ORANG TUA DENGAN TINDAKAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK (Studi Kasus Dalam Rangka Pencegahan Kekerasan Seksual Pada Anak di Kota Mojokerto) - ANGGRENI, DHONNA; RACHMAT HARGONO, HARI BASUKI NOTOBROTO (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Cases of sexual abuse of children is one of the cases that have increased quantitatively also qualitative. The parental care in providing reproductive health education influence children’s growth and development, especially in reproductive health problems.This study aimed to analyze the relationship patterns of parenting with reproductive health behavior of children in order to prevent sexual abuse of children in Mojokerto. The research design was crosssectional. This research was conducted in Mojokerto in June 2016. The population were all students in 4th and 5th grade and their parents. The research sample of 103 people that selected using simple random sampling. Data collection was carried distributing questionnaires to the respondents. Data analyzed by using Chi Square and Fisher's Exact test. The results showed that there is a relationship between the parenting with reproductive health action in order to prevent child sexual abuse in children.Reproductive health education by parents to children can increase children's awareness and confidence that will eventually affect attitudes. If the child is already getting reproductive health education from parent, then the child will try to keep her reproductive health and trying to keep himself in order to avoid sexual violence.Keyword: parenting, behavior, reproduction, violence